2021
DOI: 10.3390/ma14102611
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Copper-Doped Mesoporous Bioactive Glass Nanospheres in Experimental Dental Composites: Chemical and Mechanical Characterization

Abstract: Experimental dental resin composites incorporating copper-doped mesoporous bioactive glass nanospheres (Cu-MBGN) were designed to impart antibacterial and remineralizing properties. The study evaluated the influence of Cu-MBGN on the mechanical properties and photopolymerization of resin composites. Cu-MBGN were synthesized using a microemulsion-assisted sol–gel method. Increasing amounts of Cu-MBGN (0, 1, 5, and 10 wt %) were added to the organic polymer matrix with inert glass micro- and nanofillers while ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…In recent years, restorative dentistry has gradually shifted from "biocompatibility" to "bioactivity". With the advancement of minimally invasive dentistry, scientific interest in restorative materials with ion release also increases [1][2][3][4][5]. Restorative materials should possess anti-demineralizing and remineralizing properties to fight against caries while retaining their stability over time and resistance to occlusal load, thermal changes, and enzymatic influences in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, restorative dentistry has gradually shifted from "biocompatibility" to "bioactivity". With the advancement of minimally invasive dentistry, scientific interest in restorative materials with ion release also increases [1][2][3][4][5]. Restorative materials should possess anti-demineralizing and remineralizing properties to fight against caries while retaining their stability over time and resistance to occlusal load, thermal changes, and enzymatic influences in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Research on ion-releasing dental restorative materials is expanding. The term ‘bioactivity’ has increasingly been used in connection with dental restorative materials in original research over the past decade [ 1 , 2 ], and various attempts have been made to produce a strong and durable material with bioactive properties [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adding Cu-MBGN improved the flexural strength and microhardness of the composites. Water immersion for 28 days did not reduce the flexural strength of experimental materials containing combined silanised silica particles and Cu-MBGN, but such stability was not observed for materials containing only Cu-MBGN [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers may explore the controlled and optimum therapeutic release of copper ions for an optimum clinical outcome. A study reported copper-doped mesoporous bioactive glass nanosphere-incorporated resin exhibited antimicrobial properties, mechanical properties, and a better aging resistance effect [ 81 ]. An etch-and-rinse adhesive with copper nanoparticles appeared to have antimicrobial activity and prevented the degradation of the adhesive interface without altering the mechanical properties [ 82 ].…”
Section: Copper Nanoparticles In Dental Materialsmentioning
confidence: 99%